2016
DOI: 10.1016/j.ijgo.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of previous ovarian drilling on cumulative ongoing pregnancy rates among patients with polycystic ovarian syndrome undergoing in vitro fertilization

Abstract: LOD could compromise cumulative ongoing pregnancy rates during subsequent in vitro fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
2
2
Order By: Relevance
“…But the same study results disagreed with our results as regard the percentage of canceled embryo transfer as they found that the rate of cancelled embryo transfer was significantly higher among patients in no LOD group in comparison with the LOD group (P-value= 0.016) (16).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…But the same study results disagreed with our results as regard the percentage of canceled embryo transfer as they found that the rate of cancelled embryo transfer was significantly higher among patients in no LOD group in comparison with the LOD group (P-value= 0.016) (16).…”
Section: Discussioncontrasting
confidence: 99%
“…Cai, et al [16] , their results came in agreement with our current study regarding the number and quality of embryos transferred (no significant difference in percentages of patients in both study groups).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In cases of isolated CC-resistant PCOS, drilling can be proposed before a medical ovulation induction treatment. In cases of associated infertility factors it is more difficult to pinpoint the best time for ovarian drilling [[42], [43], [44]].…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study was conducted by Cai et al 70 to determine if history of undergoing LOD affects cumulative ongoing pregnancy rates following IVF in patients with PCOS. The study included 110 patients in the LOD group, 127 patients in the no-LOD group, and 990 patients in the age-matched group.…”
mentioning
confidence: 99%